Development of a half-bridge LLC DC-DC loaded resonant converter for low power application / Mazliza Abdul Halim - Abdul Halim, Mazliza (2018)
An LLC DC-DC loaded resonant converter is gaining more attention in power-supply designs due to its potential to achieve high efficiency and power density. Due to complex resonant circuit behaviour, the design method of LLC converter becomes complicated and difficult. In the past, there are many studies have presented the design methods of LLC converter to facilitate the design work. However, those studies only applied LLC converter for medium power application and never been applied for low power application. Besides that, LLC converter has been designed with small magnetising inductance value (μH) which led the converter to high conduction loss. Therefore, this study presents details LLC converter design method with large magnetising inductance (mH) which applies for low power application. The FHA method is used to analyse and design the converter while MATLAB/Simulink software is utilised to verify the converter design. The prototype circuit of half bridge LLC DC-DC loaded resonant converter with 30mW/3V output is then fabricated and tested. The results at switching, resonant tank, rectifier and load stages successfully verified with theoretical, simulation and experimental works and converter also successfully achieved lowest switching loss.